Once forbidden, twice tempted - Booth, Karen (Karen B.) (Booth, Karen (Karen B.). Sterling wives., 2020)
"Real estate agent Tara Sterling jumps at the chance to start fresh when she inherits part of her late ex-husband's company. But claiming her rightful place at Sterling Enterprises means working side-by-side with CEO Grant Singleton, her ex's best friend. Their long-simmering heat spells trouble as both vie for control of the business--and lose control of their thirst for each other..." --Amazon.